Design of Laboratory Algorithm Model for Grid Backbone - HUANG Xiao-ming; CHE Jian-tao; FAN Bing; LI Xin-qi (Journal of Harbin University of Science and Technology)
The transmission network is the core of the power network and plays an important role in the power network planning and defense. According to different node weights and elements of the transmission network, different algorithm models can be used to conduct in-depth research on specific problems. Based on the node topology importance, this paper establishes the importance index of different load nodes in the transmission network, and demonstrates the evolutionary construction method of the backbone grid of the transmission network. Through the improved Dijkstra algorithm, the shortest path from the initial node to the terminal node is obtained and the shortest path from the initial node to any node is obtained. The existing data of the project team in the laboratory is taken as an example for simulation and a concise analysis of the experimental results. The results show that the improved Dijkstra algorithm combined with the simplified model of the grid backbone architecture can effectively reflect the structure of the transmission network, thus establishing the backbone grid model of the transmission network. Compared with the backbone network analysis of the laboratory case, the reliability of the algorithm and model is verified, which has a forward-looking significance for the development and design planning of the future grid.